Integrating equity indicators for hospital reporting metrics - Aliya Allen-Valley; Shalu Bains; Karen Rai; Nirmal Summan; May Eleid; Emmalin Buajitti; Laura C. Rosella (Research in Health Services & Regions, 2024)
Abstract Disparities in healthcare delivery and design are deeply-rooted within healthcare systems globally. Many researchers have developed methods to measure inequity; however, there currently exists no accepted measurement approach implemented consistently across health systems. We applied the model-based Relative Index of Inequality (RII) as a measure of inequity at one of Canada’s largest health systems, Trillium Health Partners, across two service types: planned and outpatient. Our RII estimates suggest that the lowest-SES individuals received planned and outpatient services at rates 2.4 times and 2.5 times lower than the highest-SES individuals, respectively. Across both service types, the largest disparity was for breast cancer screening, where patients from the lowest-SES neighbourhoods were 5.4 times less likely to use this service at THP. These findings further underscore the importance of consistently measuring and monitoring inequities to develop effective strategies to address the health needs of patients from lower SES neighbourhoods. The approach used within this study should be considered for widespread integration into health system reporting metrics.